Molecular Aspects of Dendritic Cell Activation in Leishmaniasis: An Immunobiological View - Tibúrcio, Rafael; Nunes, Sara; Nunes, Ivanéia; Rosa Ampuero, Mariana; Silva, Icaro Bonyek; Lima, Reinan; Machado Tavares, Natalia; Brodskyn, Cláudia (Frontiers in Immunology, 2019)
Dendritic cells (DCs) are a diverse group of leukocytes in charge of bridging innate and adaptive immunity. Despite their functional versatility, DCs exist primarily in two basic functional states: quiescent and activated. A large body of evidence suggests that upon interactions with pathogens, DCs undergo intricate cellular processes that culminate in their activation, which is paramount for the orchestration of appropriate immune responses against Leishmania parasites. Herein we propose a concise review of the emerging hallmarks of DCs activation in Leishmaniasis, bringing a comprehensive discussion of the following molecular events underlying such phenomenon: DC-Leishmania interaction, antigen uptake, expression of co-stimulatory molecules, ability to migrate, antigen presentation, metabolic reprogramming, and epigenetic alterations.